2020
DOI: 10.3390/cancers12092715
|View full text |Cite
|
Sign up to set email alerts
|

Menin and Menin-Associated Proteins Coregulate Cancer Energy Metabolism

Abstract: The interplay between glycolysis and mitochondrial oxidative phosphorylation (OXPHOS) is central to maintain energy homeostasis. It remains to be determined whether there is a mechanism governing metabolic fluxes based on substrate availability in microenvironments. Here we show that menin is a key transcription factor regulating the expression of OXPHOS and glycolytic genes in cancer cells and primary tumors with poor prognosis. A group of menin-associated proteins (MAPs), including KMT2A, MED12, WAPL, and GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In order to address this question, pharmacological formulations, pharmacokinetic studies, and long-term toxicity in other species should be investigated in the following studies. More intriguingly, the type of thiophenpyrimidine inhibitors was also revealed to be effective in inhibiting the proliferation of solid tumors, including prostate cancer [ 5 , 29 ], liver cancer [ 6 ], breast cancer [ 27 ], lung cancer [ 23 ], and osteosarcoma [ 50 ]. However, the molecular mechanism of these menin/MLL1 small molecules inhibiting the proliferation of solid tumor cells is not clear, and it can be roughly understood that they have a synergistic effect with tumor chemotherapy drugs and may participate in the signaling pathway of chemotherapy drugs to inhibit tumors, which comprises speculation and needs to be further proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to address this question, pharmacological formulations, pharmacokinetic studies, and long-term toxicity in other species should be investigated in the following studies. More intriguingly, the type of thiophenpyrimidine inhibitors was also revealed to be effective in inhibiting the proliferation of solid tumors, including prostate cancer [ 5 , 29 ], liver cancer [ 6 ], breast cancer [ 27 ], lung cancer [ 23 ], and osteosarcoma [ 50 ]. However, the molecular mechanism of these menin/MLL1 small molecules inhibiting the proliferation of solid tumor cells is not clear, and it can be roughly understood that they have a synergistic effect with tumor chemotherapy drugs and may participate in the signaling pathway of chemotherapy drugs to inhibit tumors, which comprises speculation and needs to be further proven.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to OXPHOS, this transient inhibition had less effect on glycolysis and was quickly recovered. Thus, the MI-503 treatment significantly reduced the amount of ATP produced by OXPHOS, but the existing glycolytic enzymes continued to function and were able to compensate for the energy loss [ 27 ].…”
Section: Type Of Thiophenpyrimidine Inhibitorsmentioning
confidence: 99%
“…We have speculated that the appearance of those CD8 + T cells is the result of epigenetic changes driven by certain histone modifications such as downregulation of the histone acetyltransferase Kat2b (which is expected to increase ribosome biogenesis) and downregulation of histone methyltransferase Kmt2a (which is expected to enhance OXPHOS) (Fig. 5E) (51,52). As an immuno-tuning tool, BCAT1i can be used either in a CAR-T cell setting, prior to the cell transfer to prevent and/or suppress the rise of an exhaustive phenotype in the CAR-T cells, or in combination with an ICI, to increase the cytotoxicity of reinvigorated CD8 + T cells in the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Menin protein is a cofactor of leukemia caused by MLL fusion proteins. Numerous studies have indicated that the interaction between menin and the MLL fusion proteins is involved in the development of leukemia induced by MLL fusion proteins. As a tumor suppressor encoded by multiple endocrine tumor type 1 gene (MEN1), menin consists of 610 residues and is recognized as a scaffold protein involved in the protein–protein interaction network. The crystal structure of menin is like a curved left-hand, in which the N-terminal domain is depicted as a thumb, the middle region adopts the shape of the palm, and the C-terminus resembles curved fingers (Figure A and B) . Notably, the palm forms a deep pocket that is occupied by the conserved MLL MBM (MLL menin-binding motif), which is the N-terminus motif of MLL consisting of residues 6–25.…”
Section: Menin Proteinmentioning
confidence: 99%